The dark tide - Jasinska, Alicia (Sourcebooks Fire, 2020)
Sixteen-year-old Lina Kirk sacrifices herself to her sinking island's Witch Queen, Eva, to save her brother and her secret crush, but when she and Eva fall in love, everyone is in danger.